Comparative study of friction stir welding process and its variables. (2020) - Vetrivel Sezhian, M.; Ramadoss, R.; Giridharan, K.; Chakravarthi, G.; Stalin, B.
Abstract: The Friction Stir Welding (FSW) process is an attractive material combined technique for similar and different alloys without material losses. The legend Wayne Thomas is the father of the FSW technique. At 1991 the material joining process was initiated and filed patents by the TWI Welding Institute in the UK. Initially, the FSW process was utilized to fabricate dissimilar weld joints. This material joining technique provides enormous advantages in aluminium alloy related components. The friction stir welding process has become a major material combining process without using the additional filler material. During material joining, the process does not release any type of gases and fumes. This material joining technique is a solid-state joining process and which is an environment-friendly. The solid-state joining process is utilized with a non-consumable rotating tool while joining two similar and dissimilar metals. This article looks, at an overview of friction stir welding process and variables such as tool revolving rate, tool travelling speed, different pin profiles, tool tilt angle, and axial loading conditions for joining of material joints. These FSW process variables, decide the quality of weld joints. Recently worldwide, more than 135 licenses have been filed for the FSW process. In the routine process, several new techniques and applications are being developed in the material joining process. A massive joining process (FSW) is recently widely utilized in the area of various applications like aeronautical, shipbuilding, rail manufacturing industries, especially for aluminium-related weld joints. In addition to the applications of FSW, various aspects and a number of key troubles are also discussed.